2017
DOI: 10.1038/srep46393
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity and accuracy of high-throughput metabarcoding methods for early detection of invasive fish species

Abstract: High-throughput DNA metabarcoding has gained recognition as a potentially powerful tool for biomonitoring, including early detection of aquatic invasive species (AIS). DNA based techniques are advancing, but our understanding of the limits to detection for metabarcoding complex samples is inadequate. For detecting AIS at an early stage of invasion when the species is rare, accuracy at low detection limits is key. To evaluate the utility of metabarcoding in future fish community monitoring programs, we conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 52 publications
2
26
0
Order By: Relevance
“…Numerous studies have highlighted variations in biological communities identified when different genes are targeted in high throughput sequencing (HTS) studies. This variation is commonly attributed to: lack of primer universality or specificity, preferential amplification of certain organisms (e.g., taxa with short sequences), incomplete or inaccurate reference databases, and differences in the levels of taxonomy that can be resolved by target genes (e.g., De Barba et al, ; Deagle et al, ; Hatzenbuhler, Kelly, Martinson, Okum, & Pilgrim, ; Wilcox et al, ). Although not a specific aim of this study, we observed marked differences in taxonomic composition of the communities when targeting the COI and 18S rRNA gene.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have highlighted variations in biological communities identified when different genes are targeted in high throughput sequencing (HTS) studies. This variation is commonly attributed to: lack of primer universality or specificity, preferential amplification of certain organisms (e.g., taxa with short sequences), incomplete or inaccurate reference databases, and differences in the levels of taxonomy that can be resolved by target genes (e.g., De Barba et al, ; Deagle et al, ; Hatzenbuhler, Kelly, Martinson, Okum, & Pilgrim, ; Wilcox et al, ). Although not a specific aim of this study, we observed marked differences in taxonomic composition of the communities when targeting the COI and 18S rRNA gene.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to marker choice, we used 18S in our study but COI has shown higher sequence variability and improved taxonomic assignment (Hatzenbuhler et al, 2017;Tang et al, 2012;Zhan, Bailey et al, 2014). This variability can be a double-edged sword; as it is apparent even in primer binding sites, COI can have issues with primer generality (Deagle et al, 2014;Ficetola et al, 2010;Hatzenbuhler et al, 2017;Zhan, Bailey et al, 2014). Consequently, false-negative errors may be more likely to occur because of inconsistent amplification which would be particularly detrimental to early detection of AIS.…”
Section: Discussionmentioning
confidence: 99%
“…Primers for this marker effectively amplify a broad range of zooplankton taxa, making 18S a suitable marker for zooplankton metabarcoding studies (Zhan, Bailey, Heath, & MacIsaac, 2014). Conversely, the COI marker is highly variable for these taxa (sometimes, even in the primer binding sites) which may make it more suitable for studies taking the targeted approach than for metabarcoding highly divergent communities (Deagle, Jarman, Coissac, Pompanon, & Taberlet, 2014;Hatzenbuhler, Kelly, Martinson, Okum, & Pilgrim, 2017;Zhan, Bailey et al, 2014). The drawback of 18S is that due to lower variability, it may be more difficult to assign identity at the species level.…”
Section: Dataset Preparationmentioning
confidence: 99%
“…whereas sediment/benthos or soil samples are termed "bulktissue DNA" (Hatzenbuhler et al, 2017;Hajibabaei et al, 2019;Harper et al, 2019), despite these types of sample all referring to DNA which is isolated from an environmental sample (Dickie et al, 2018). This lack of consistency is particularly challenging when attempting to amalgamate literature and compare studies from different research groups and for effectively communicating results of DNA-based studies to non-specialists.…”
Section: First Termmentioning
confidence: 99%